(untitled) (Research, Society and Development, 2022)
Leprosy is a chronic granulomatous infectious disease of the skin and peripheral nervous system caused by Mycobacterium leprae. This disease has a wide spectrum of clinical presentations, and its diagnosis is mainly based on the presence of skin lesions, loss of sensation and neural thic. It is a serious public health problem, endemic in Brazil and highly prevalent in Bahia. In that scenario, to contribute to the prevention and to the disease’s control actions in the state, this study is aimed to describe the epidemiological profile of leprosy in Bahia from 2010 to 2020. This is a descriptive epidemiological study, which data was obtained by consulting the Sistema de Informação de Agravos de Notificação (SINAN), made available by the Departamento de Informática do Sistema Único de Saúde (DATASUS). Between 2010 and 2020, 30,426 cases of Leprosy were notified in Bahia, of which the majority were men (53%), mixed race (61%), between the 1st to 4th grade of elementary school incomplete (21.4%), in the age group of 30 to 39 years (18.3%), with five or more skin lesions (39%), who did not present a reaction episode (56%) and were treated with multidrug therapy for multibacillary using 12 doses (64%). The data indicate that leprosy in Bahia, occurs more commonly in economically active population with little access to information. The content of the present study can direct strategies to reduce the development of this disease in order to improve public health, besides reinforcing the need for similar studies.